Quarter, cow, and farm risk factors for intramammary infections with major pathogens relative to minor pathogens in Thai dairy cows - Kansuda Leelahapongsathon (2018)
A cross-sectional study was carried out from May to September 2011 on 35 smallholder dairy farms in Chiang Mai, Thailand, to identify the quarter, cow, and farm factors that relate to intramammary infections (IMI) from major specified pathogens, compared to infections from minor pathogens. Data on general farm management, milking management, and dry cow management were recorded for each herd. Quarter milk samples were collected from either clinical or subclinical mastitis quarters. Dependent variables were binary data defining the specified major pathogens, including Streptococcus agalactiae (7.1 %), Streptococcus uberis (9.4 %), Streptococcus dysgalactiae (4.0 %), and other streptococci (16.7 %), as a case, and all minor pathogens as a control, in each dependent variable. The occurrence of S. agalactiae IMI was lower in first-parity cows and cows with short milking time. Cows with body condition score (BCS) <2.5 had higher occurrence of S. agalactiae IMI. The occurrence of S. uberis IMI was higher in quarters with California mastitis test (CMT) score 2, score 3, and having clinical mastitis and in farms with increasing age of vacuum system. Quarters with CMT score 3, having clinical mastitis, cow with manual milking after detaching milking cluster, and farms with high bulk milk somatic cell counts (BMSCC >500,000 cells/ml) had higher occurrence of S. dysgalactiae IMI. For other streptococci, quarters having clinical mastitis, BCS <2.5, and pulling down of milking cluster while milking increased occurrence of other streptococci IMI relative to minor pathogen IMI. These results highlight the importance of individual cow factors, milking characteristics, and BMSCC in determining the risk of IMI from major pathogens. © 2014 Springer Science+Business Media Dordrecht.